2010
DOI: 10.1002/cncr.24817
|View full text |Cite
|
Sign up to set email alerts
|

Race, ethnicity, and socioeconomic status influence the survival of patients with hepatocellular carcinoma in the United States

Abstract: BACKGROUND: Racial, ethnic, and socioeconomic disparities in the survival of patients with hepatocellular carcinoma (HCC) continue to exist. The authors of this report hypothesized that these differences result from inequities in access to care and in response to therapy. METHODS: Patients with HCC (n ¼ 20,920) were identified from the Surveillance, Epidemiology, and End Results (SEER) database, and patients who underwent liver transplantation for HCC (n ¼ 4735) were identified from the United Network for Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
182
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(203 citation statements)
references
References 29 publications
16
182
1
1
Order By: Relevance
“…Patient knowledge, attitudes, and barriers of this population are particularly important to understand given increased HCC risk, lower surveillance rates, and worse prognosis among racial/ethnic minorities and patients of low SES. (4,23,24) Despite differences in patient populations, patients demonstrated high levels of basic knowledge regarding HCC risk, surveillance logistics, and prognosis. Most important, 90% of patients understood that cirrhosis is a high-risk state for HCC and that ultrasound-based surveillance should be performed every 6-12 months.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Patient knowledge, attitudes, and barriers of this population are particularly important to understand given increased HCC risk, lower surveillance rates, and worse prognosis among racial/ethnic minorities and patients of low SES. (4,23,24) Despite differences in patient populations, patients demonstrated high levels of basic knowledge regarding HCC risk, surveillance logistics, and prognosis. Most important, 90% of patients understood that cirrhosis is a high-risk state for HCC and that ultrasound-based surveillance should be performed every 6-12 months.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…8,9 One of these studies, using data from 1998 through 2002, also found that API patients with LT-eligible HCC were approximately half as likely as whites to undergo LT. 8 Another study using data from the SEER and OPTN databases found that among HCC patients who underwent LT, AA patients had the worst graft survival and overall survival. 10 Racial disparities in the use of LT extend well beyond patients with HCC. In a national study using data from 1998 through 2003, AA patients with end-stage liver disease were less likely than whites to be listed for LT and once listed, less likely to undergo LT.…”
mentioning
confidence: 99%
“…During data collection and database construction, we found that there were few reports investigating the association between genetic variations and HCC progression, drug response, survival, or recurrence. To date, these therapy-related parameters have been reported to vary among individuals (Artinyan et al, 2010;Huynh, 2010;Tanaka and Arii, 2010;Worns and Galle, 2010). Thus, it is important and urgent for researchers to accelerate investigation in these areas.…”
Section: Database Contentsmentioning
confidence: 99%
“…To date, the detailed pathogenesis of HCC is still under OFFICIAL JOURNAL www.hgvs.org investigation and clinical therapies for this disease are limited and mostly inefficient (Thorgeirsson and Grisham, 2002;Llovet et al, 2003;Farazi and DePinho, 2006;Whittaker et al, 2010). Among the problems faced by researchers, are the distinct susceptibilities of HCC worldwide (Kew, 2002;El-Serag and Rudolph, 2007), the dissimilar responses to common therapies between individuals (Worns and Galle, 2010), and the diverse survival and recurrence rates in different populations (Artinyan et al, 2010). This diversity is partially due to human genetic variations such as mutations, polymorphisms, and mtDNA copy number (Wong et al, 2000;Sheen et al, 2003;Lee et al, 2004;Kirk et al, 2005;Yamada et al, 2006;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%